Elevated Serum Levels of Vitamin D in Infants With Urolithiasis (Iranian Journal of Kidney Diseases, 2012)
Introduction. The pathophysiology of urolithiasis in infancy is not well known. The aim of this study was to investigate whether infants with urolithiasis have higher serum levels of vitamin D, as a possible risk factor for urolithiasis, compared to infants without urinary calculi. Materials and Methods. In this case-control study, 36 infants with urolithiasis (age range, 2.5 to 24 months) were enrolled as well as 36 age- and sex-matched infants without urolithiasis. Random urine samples were tested for calcium, phosphorous, oxalate, citrate, uric acid, sodium, potassium, magnesium, and creatinine levels, and also nitroprusside test was done on the samples. Serum levels of potassium, urea nitrogen, creatinine, 25-hydroxyvitamin D3, parathyroid hormone, calcium, phosphorous, and uric acid were measured in all of the infants with urolithiasis. Serum levels of 25-hydroxyvitamin D3 were also measured in the control group. Results. Serum levels of 25-hydroxyvitamin D3 were significantly higher in the infants with urolithiasis than in the controls (33.85 ± 14.78 ng/mL versus 18.26 ± 7.43 ng/mL, P < .001). Nine infants in the urolithiasis group (25%) were found to have hypercalcemia; 3 of these cases also had hypervitaminosis D. Hypercalciuria was detected in 10 infants with urolithiasis (27.8%), hypocitraturia in 6 (16.7%), hypomagnesiuria in 3 (8.3%), and hyperoxaluria in 1 (2.8%). Nineteen infants with urolithiasis had at least one metabolic disorder. Conclusions.   High serum levels of vitamin D may play an important role in the pathogenesis of urolithiasis in infants with hypercalcemia. We recommend evaluation of vitamin D levels in these infants.